COVID-19 pandemisinin İstanbul'un Şile ilçesinde hava kalitesine (PM10) etkisi - ÖZVEREN, UĞUR (My University, 2022)
The first COVID-19 case in Turkey was approved on March 11, 2020. Based on the rapid spread feature of the COVID-19 pandemic, a partial lockdown was put into practice in the whole of İstanbul for the weekends from March 21st to June 1st, 2020. The application of strict restriction precautions enabled us to decrease the effect of the COVID-19 pandemic on the Turkey National Health System while changing social behaviors. On the other hand, these forced measures provided an opportunity to determine the impact of anthropogenic events on air quality based on controlling pollution levels. The main goal of the present study is to examine the effect of the partial lockdown precautions on the pattern of air quality in the Şile district of İstanbul. The analysis of the air quality was carried out with the aid of air quality data from the monitoring station in Şile that contains PM10 concentration. The results showed an increase of approximately 16.90% in PM10 concentrations in Şile. This was ascribed to the increment of vehicle traffic and human mobility due to the migration from other districts of İstanbul during the COVID-19 outbreak. It is considered that the rural and characteristic properties of the district are among the reasons for taking immigration from the other districts of İstanbul during the COVID-19 outbreak. This study examines the impacts of the psychological behavioral changes and the restrictions related to the pandemic on air pollution. Keywords: COVID-19, Lockdown, Air quality, PM Concentration, Şile district, Istanbul

Türkiye'deki ilk COVID-19 vakası 11 Mart 2020'de onaylandı. COVID-19 salgınının hızlı yayılma özelliğine bağlı olarak, 21 Mart - 1 Haziran 2020 tarihleri arasında İstanbul genelinde hafta sonları için kısmi kısıtlama uygulamaya konuldu. Sıkı kısıtlama önlemlerinin uygulanması, sosyal davranışları değiştirirken COVID-19 Türkiye Ulusal Sağlık Sistemi üzerindeki etkisini azaltmayı sağladı. Öte yandan, bu zorunlu önlemler insan kaynaklı olayların havat kalitesi üzerindeki etkisini kirlilik seviyelerini kontrol etmeye bağlı olarak belirleme fırsatı sağladı. Bu çalışmanın temel amacı, kısmi kısıtlama önlemlerinin İstanbul'un Şile ilçesi hava kalitesi üzerine etkisini incelemektir. Hava kalitesi analizi, Şile'deki izleme istasyonunun PM10 konsantrasyonu içeren hava kalitesi verileri yardımıyla gerçekleştirildi. Sonuçlar, Şile'nin PM10 konsantrasyonlarında yaklaşık % 16.90 artış olduğunu gösterdi. Bu, COVID-19 salgını sırasında İstanbul'un diğer ilçelerinden göç nedeniyle araç trafiğinin ve insan hareketliliğinin artmasıyla ilişkilendirildi. İlçenin kırsal karakteristik özelliklerinin COVID-19 salgını sırasında İstanbul'un diğer ilçelerinden göç alma sebepleri arasında olduğu değerlendirilmektedir. Bu çalışma, pandemi ile ilgili psikolojik davranış değişikliklerinin ve kısıtlamaların hava kirliliği üzerindeki etkilerini incelemektedir. Anahtar Kelimeler: COVID-19, Kısıtlama, Hava kalitesi, PM Konsantrasyonu, Şile ilçesi, İstanbul
The Impact of the COVID-19 Pandemic on the Air Quality (PM10) in Şile District of Istanbul, Turkey
Keywords: COVID-19; Lockdown; Air quality; PM Concentration; Şile district; Istanbul; Kısıtlama; Hava kalitesi; PM Konsantrasyonu; Şile ilçesi; İstanbul